Health Literacy and COVID-19 preventive behaviours in during the Lock-Down Phase in Tuscany (Italy). (20th October 2021) - Del Riccio, M; Lastrucci, V; Bechini, A; Boccalini, S; Chiesi, F; Gori, E; Lorini, C; Moscadelli, A; Zanella, B; Bonaccorsi, G
Abstract: : In the first COVID-19 pandemic period, when no vaccines were available, individual behaviours were essential for controlling the spread of the virus. In this context of rapidly changing guidance, emerging new evidence, fake news and misinformation, there have been new challenges for health literacy (HL). This study explored whether guidance-compliant healthy behaviours were associated with HL in individuals who have performed essential activities (public employees and volunteers of the Civil Protection) during the lock-down period in the Province of Prato, Italy. Items on knowledge, attitudes and practices (KAP) towards COVID-19 preventive measures and COVID-19 risk perception, along with the Italian version of the 6-items European Health Literacy Survey Questionnaire (HLS-EU-Q6), were collected using a self-administered structured questionnaire. In May 2020, 751 responses were collected; respondents were mostly males (59%), younger than 65 years old (83.5%), with sufficient HL (56%), and never smokers (54.2%). Most of the items related to the KAP towards COVID-19 preventive measures were significantly correlated with the HLS-EU-Q6 score in the total sample. In the multiple linear model, HL results to be a predictor of both a better self-reported knowledge of COVID-19 preventive measures (beta 0.32 for sufficient HL, 0.11 for problematic HL, 1.00 for inadequate HL) and a higher score of attitude towards the importance of COVID-19 preventive measures (beta 0.33 for sufficient HL, 0.17 for problematic HL, 1.00 for inadequate HL), while it has no role in predicting a higher risk perception. These findings can be useful to understand the importance of HL in promoting guidance-compliant healthy behaviours and in helping people to understand the rapidly changing public health messages and then act accordingly. Key messages: Lower levels of Health Literacy predict poor COVID-19 related knowledge and a worse attitudes towards the importance of COVID-19 preventive measures. Health Literacy may be an important factor in promoting guidance-compliant healthy behaviours and in helping people to understand the rapidly changing public health messages and then act accordingly.